Kinerja Organisasi Publik dalam Pemanfaatan Instagram sebagai Media Pelayanan Informasi - Sulila, Vivi Venti Vera; Hadjarati, Siti Fadillah (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
The use of social media by public organizations has become a form of transformation in public information services in the digital era. Instagram, as one of the most widely used social media platforms, is utilized by governments to deliver public service information quickly, openly, and accessibly. This study aims to determine the performance of public organizations in utilizing Instagram as a medium for information services. The research employed a qualitative approach with a descriptive method. Data collection techniques were conducted through literature studies and observations of social media usage in public services. The results indicate that the utilization of Instagram helps public organizations deliver service information, improve interaction with the community, expand public access to information, and support service transparency. However, the utilization of social media in public services still faces obstacles such as limitations in digital communication management, suboptimal service responses, and low levels of public digital literacy. Therefore, public organizations need to improve social media management so that digital-based public information services can operate more effectively and responsively.